Prevalence and Pattern of Non-Syndromic Hypodontia in a Group of Turkish Children - KARGÜL, BETÜL (UNIV ZAGREB, SCH DENTAL MEDICINE, 2016)
Objective: The aim of this study was to assess the prevalence and pattern of congenital missing teeth in the permanent dentition (excluding wisdom teeth), among Turkish children in a 4-year period (2009-2012). Methods: The study group comprised 1658 children (873 girls, 785 boys). The children were examined in Department of Pediatric Dentistry, Dental School of Marmara University. A chi square test was used to determine the difference in the prevalence of hypodontia between genders. Results: The prevalence of hypodontia was 6.2% (6.3% girls, 6% boys) with no statistically significant difference between the genders (P=0.601). The most frequently missing tooth were the mandibular left second premolars, 63 (20.7%), followed by the mandibular right second premolars, 61(20.1%), maxillary left premolars, 31 (10.2%). There were 89 anterior and 214 posterior missing teeth. Bilateral hypodontia was observed in 70 (39 girls, 31 boys) patients (67.9%). The most common bilateral missing teeth were the mandibular second premolar (22 girls, 21 boys) (42.1%) and the maxillary second premolar (6 girls, 15 boys) (20.5 %). The mandibular left second premolar (9 boys, 8 girls) was the most frequent unilaterally missing tooth (5.6 %) followed by the mandibular right second premolar (10 girls, 6 boys) (5.28 %). Conclusion: The obtained results point to the importance of detailed clinical and radiographic examination. These help with long-term treatment planning according to a child's individual requirements.
Keywords: Hypodontia; Anodontia; Child; Turkey